Standardized ileal digestibility of amino acids of protein sources associated with exogenous enzymes for broilers - Bruno Duarte Alves Fortes; Heloisa Helena de Carvalho Mello; Marcos Barcellos Café; Emmanuel Arnhold; José Henrique Stringhini (Animal Bioscience, 2022)
Objective Two experiments were conducted to evaluate the effect of enzyme complex (EC) on the standardized ileal digestibility (SID) of amino acids (AA) in corn gluten meal (60%) (CGM), soy protein concentrate (SPC), dried bovine plasma (DBP), and poultry offal meal (POM). Experiments I and II were conducted with broilers in the pre-starter (1 to 7 days of age) and starter (1 to 21 days of age) phases, respectively. Methods The treatments consisted of a protein-free diet (PFD) containing feedstuffs either supplemented with EC (xylanase, amylase, and protease) or not. In Experiment I, a total of 360 one-day-old male Cobb-500 broiler chicks were randomly housed in 45 pens, resulting in five replicates with eight birds each, totalizing eight treatments and one PFD group. In Experiment II a total of 270 one-day-old male Cobb-500 broiler chicks were randomly housed in 45 pens, resulting in five replicates with six birds each, totalizing eight treatments and one PFD group. The PFD groups were used to assess the endogenous AA losses. The birds were slaughtered to collect the ileal content. Results In the pre-starter phase, the SID of arginine, branched chain-aminoacids, glycine, serine, aspartate, and glutamic acid increased with EC addition. The EC improved the SID of arginine and glutamic acid of CGM; the SID of valine and cystine of SPC; the SID of leucine, glycine, and aspartate of POM and the SID of isoleucine of DBP. In the starter phase, the SID of isoleucine, phenylalanine and glycine increased in EC-supplemented diets. The EC improved the SID of isoleucine of DBP; the SID of phenylalanine of CGM and POM. The SID of AA of SPC was not influenced by the EC. Conclusion The addition of an EC to broiler pre-starter and starter diets is efficient in increasing the SID of AA on SPC, POM, and DBP.